PEMBINAAN PENGERAJIN BOKOR ALUMINIUM DI DESA MENYALI - ANTARA, dkk., I NYOMAN GDE (Buletin Udayana Mengabdi, 2014)
Alluminium bowl craft industrial center is located in Menyali village Sawan district Buleleng regency of Bali province. In this business development, they faced some problems such as increasingly expensive alluminium plate raw materials, decreasing selling product prices due to competition among craftsmen, difficulty in extending the marketing, lack of capital, lack of knowledge in business management, and lack of technical capacity and production innovation. Currently the organization has been formed aluminum bowl craftsmen groups, they are “Sumber Urip” and “Sumur Jaya”. This organization is still limited to tradisional associations such as a community organization, has not led to organize in a micro-enterprise or cooperation. Their organization management should not be arranged. Therefore, they need helps from the government and other institutions to build this bowl craftsmen in developing their businesses through a group of micro-enterprises or cooperations. Wishly, with formal business entity that would facilitate access to a variety of coaching and help governments and other institutions. From the SWOT analysis, it is found some problems and solutions that should be done. Alluminium bowl craftsmen groups, named “Sumber Urip” and “Sumur Jaya” is not in the form of business entity or cooperation yet, so that the results of coaching have agreed to form a cooperation. Venture capital assistance for the development and production are still needed and to be an absolute given, but a way to market more absolute yield is given, through participation in various events exhibition to introduce the product is expected to expand its market share up to overseas or exports. In the production process it has been introduced that is appropriate technology for instant a rolling tool to make a wiring groove on the outside of the bowl, so that it will simplify and speed up the process, especially by aged mothers. Keywords: aluminium bowl, Menyali village, SWOT analysis, appropriate technology, craftsmen coaching